Um dia da caça, outro do caçador: interações presa predador para a formação Luján (Pleistoceno da Argentina) - (:unkn) unknown (Universidade Federal do Pampa, 2019)
Predator-prey interactions have a key role in the structure of living communities, and despite being a poorly studied topic, the same is valid for extinct faunas. Here, we use a mathematical model of predator-prey interactions based on estimated body mass to the mammal fossil diversity from the Guerrero Member of the Luján Formation, Late Pleistocene from Argentina. This unit has a diverse sample of extinct and living mammal species. Our model consists in random encounters between potential prey and predator, and the hunt success rate is determined by the animal’s body mass. Diverse alterations in niche restrictions were applied, as well as simulations of hunting grouping. Here we measure the mortality rates of prey according to the predator niche amplitude, utilizing 30 prey species and 4 predator species divided in four size classes. For this data matrix, our results show that predators would favour generalist habits when hunting alone and would rarely attack large-sized prey, the latter only being attacked by groups.
Keywords: Megafauna; Modelos Computacionais; Predação; Interações Ecológicas; Computational Models; Predation; Ecological Interactions; CNPQ::CIENCIAS BIOLOGICAS